ANALISIS PENGARUH KUALITAS AUDIT TERHADAP MENEJEMEN LABA STUDI PADA PERUSAHAAN YANG MELAKUKAN IPO DI INDONESIA - Luhgiatno . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2010)
The purpose of this research is to investigate and get empirical evidence about auditor big four and auditor industry specialist in the earning management limit by the firms audited for IPO firms. The information asymmetry is participate IPO policy disposed action from management is opportunistic characteristic to execute manipulate performance with earning management. Management want to get high accountability about finance performance from audited result good auditor. Auditor want to work with professional for good performanceto keep reputation. Audit quality from auditors good reputation will more guarantee about accountability finance performance firms is audited.The Object of this research is Indonesia IPO firms. The method of data collection is purposive sampling method and resulted 37 firms observation. Regression linier is used to analysis data and develop the theory model.The result indicates that auditor big four and auditor industry specialist do not evidence can limit earning management for firms is audited when IPO firms.